REKAYASA PEMBELAJARAN IPA SUB BAB ANATOMI MANUSIA (ANTROPOTOMI) BERBASIS MULTIMEDIA - Ahmadi, Farid (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2012)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; mso-fareast-font-family:Calibri; –> <!–[endif] –> The generally educational system that has been there in todays school is very bordered in using the classroom and the time of study and also the certain meeting. When the teacher closing the class, the study is over. The characteristics in every students are different. The smartest students can’t explore their mind according to the materials that he got. The steps of the study is viewed from the activities in class, not from the students in this case. The educational that has been there is conventional education that giveless the freedom to the students interacted and exploring their mind. That’s the reason why this research is need to be doing. The aim of this research is to create a study system with the human anatomy as the material for the Class XI senior High School passing over study system of human anatomy ( Antropotomi ), basic on interactive multimedia technology. This is aimed that students can get the clearly visualization, controlling, evaluation, feedback, and also the teacher can give a consultative serve and attention to the studying of material human anatomy. The product that has been done is tested to the students and analyzed with the purpose to get the result is tis system can be applicated to fixed the problems or not. Password : thesis, multimedia, learning, antropotomi